Superextensions of cyclic semigroups - Gavrylkiv, V.M. (Carpathian Mathematical Publications, 2013)
Given a cyclic semigroup $S$ we study right and left zeros, singleton left ideals, the minimal ideal, left cancelable and right cancelable elements of superextensions $λ(S)$ and characterize cyclic semigroups whose superextensions are commutative.